Management of patients with acute subdural hemorrhage during treatment with direct oral anticoagulants - Beynon, Christopher; Brenner, Steffen; Younsi, Alexander; Rizos, Timolaos; Neumann, Jan-Oliver; Pfaff, Johannes; Unterberg, Andreas (Neurocritical care, 2019)
BackgroundAnticoagulation therapy is a major risk factor for unfavorable patient outcomes following (traumatic) intracranial hemorrhage. Direct oral anticoagulants (DOAC) are increasingly used for the prevention and treatment of thromboembolic diseases. Data on patients treated for acute subdural hemorrhage (SDH) during anticoagulation therapy with DOAC are limited.MethodsWe analyzed the medical records of consecutive patients treated at our institution for acute SDH during anticoagulation therapy with DOAC or vitamin K antagonists (VKA) during a period of 30 months. Patient characteristics such as results of imaging and laboratory studies, treatment modalities and short-term patient outcomes were included.ResultsA total of 128 patients with preadmission DOAC (n = 65) or VKA (n = 63) intake were compared. The overall 30-day mortality rate of this patient cohort was 27%, and it did not differ between patients with DOAC or VKA intake (26% vs. 27%; p = 1.000). Similarly, the rates of neurosurgical intervention (65%) and intracranial re-hemorrhage (18%) were comparable. Prothrombin complex concentrates were administered more frequently in patients with VKA intake than in patients with DOAC intake (90% vs. 58%; p < 0.0001). DOAC treatment in patients with acute SDH did not increase in-hospital and 30-day mortality rates compared to VKA treatment.ConclusionsThese findings support the favorable safety profile of DOAC in patients, even in the setting of intracranial hemorrhage. However, the availability of specific antidotes to DOAC may further improve the management of these patients.
First Online: 31 October 2018
Gesehen am 05.04.2019